HTLV-1 Transmission and HIV Pre-exposure Prophylaxis: A Scoping Review - Bradshaw, Daniel; Taylor, Graham Philip (Frontiers in Medicine, 2022)
HIV pre-exposure prophylaxis (HIV-PrEP) is effective in reducing the likelihood of HIV acquisition in HIV-negative people at high risk of exposure. Guidelines recommend testing for sexually transmitted infections (STIs) before starting, and periodically on PrEP, including bacterial infections, HIV, hepatitis C virus, and, for those who are non-immune, hepatitis B virus. Diagnosed infections can be promptly treated to reduce onward transmission. HTLV-1 is not mentioned; however, it is predominantly sexually transmitted, causes adult T-cell leukaemia/lymphoma (ATL) or myelopathy in 10% of those infected, and is associated with an increased risk of death in those without any classically HTLV-associated condition. The 2021 WHO Technical Report on HTLV-1 called for the strengthening of global public health measures against its spread. In this scoping review, we, therefore, (1) discuss the epidemiological context of HIV-PrEP and HTLV-1 transmission; (2) present current knowledge of antiretrovirals in relation to HTLV-1 transmission prevention, including nucleos(t)ide reverse transcriptase inhibitors (NRTIs) and integrase strand transfer inhibitors (INSTIs); and (3) identify knowledge gaps where data are urgently required to inform global public health measures to protect HIV-PrEP users from HTLV-1 acquisition. We suggest that systematic seroprevalence studies among PrEP-using groups, including men who have sex with men (MSM), people who inject drugs (PWIDs), and female sex workers (FSWs), are needed. Further data are required to evaluate antiretroviral efficacy in preventing HTLV-1 transmission from in vitro studies, animal models, and clinical cohorts. PrEP delivery programmes should consider prioritizing the long-acting injectable INSTI, cabotegravir, in HTLV-1 endemic settings.